ANALISIS PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI KERJA, KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. MEGA BINTANG MAS INDONESIA MEDAN - Simbolon, Sahat (Jurnal Manajemen dan Bisnis, 2022)
This study aims to describe the effect of transformational leadership, work motivation, and job satisfaction on employee performance at PT. Mega Bintang Mas Indonesia Medan. The population in this study is 72 (seventy two) and the sample is 72 using census technique. Research respondents are employees at PT. Mega Bintang Mas Indonesia Medan, which are 72 (seventy two) employees. The data research instruments used are questionnaires and documentation. The data analysis technique used is validity test, reliability test, descriptive analysis, multicollinearity test, heteroscedasticity test, Park Gleyser test, normality test, multiple linear analysis, multiple linear reliability coefficient test, partial hypothesis test or t test, simultaneous hypothesis test or test. F, and the coefficient of determination. The results of descriptive analysis at PT. Mega Bintang Mas Indonesia Medan for transformasional leadership style variable is in good category, work motivation variable is in bad category, job satisfaction variable is in very bad category and employee performance variable at PT. Mega Bintang Mas Indonesia Medan is in quite good category. Based on a partial analysis, transformational leadership, work motivation, job satisfaction have a positive and significant influence on employee performance at PT. Mega Bintang Mas Indonesia Medan. Simultaneously, transformational leadership, work motivation, job satisfaction have a positive and significant effect on employee performance at PT. Mega Bintang Mas Indonesia Medan. The contribution of transformational leadership variables, work motivation, job satisfaction to improve employee performance variables amounted to 0.566 or 56.6%, while the remaining 0.434 or 43.4% is influenced by other variables that are not examined by writer in this research, such as work environment, compensation, culture, and so on.